Aggregate Effects in Local Labor Markets of Supply and Demand Shocks - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1999)
Anti-poverty policy in the U.S. has emphasized labor supply policies, such as welfare reform or job training. Anti-poverty policy in the U.S. has not emphasized policies to increase labor demand for the poor, such as public employment or subsidizing private employers to hire the poor. What are the aggregate effects of such policies on wages and unemployment of different groups? This paper estimates and simulates a model with several types of labor, using data from the Current Population Survey on state labor markets. The simulations suggest that forcing more disadvantaged persons into the labor market can displace many other persons from employment in the short-run and medium-run, and increased public employment of the poor may be offset by reduced private employment of the poor in the long run. Wage subsidies to either the poor or the poor's employers have little effect on the poor's employment or market wages, although paying wage subsidies to the poor increases take-home pay. Finally education policies not only directly help those educated, but also increase average earnings of less-educated groups and reduce average earnings of more-educated groups.
Additional information: A revised version of this paper appears as "Spillover Effects of Welfare Reforms in State Labor Markets" in Journal of Regional Science, Vol. 42, No. 4 (November 2002), pp. 667-701.
Keywords: J0; J4; 330; local; labor; markets; supply; Bartik